The Discourse of Business Meetings Agency and Power in Financial Organizations - AlHaidari, Fatma M. (Springer International Publishing, 2018)
This book examines the social organizational discourse of task-oriented business meetings in a Kuwaiti financial organization and an American non-profit trade organisation. Focusing primarily on the linguistic behaviours demonstrating agency and power of managers and staff members displayed during these meetings, the project is based on ethnographic data collected during eight months of fieldwork. The author examines the similarities and differences between the linguistic behaviours of both organizations, particularly relating to the production of collective "we," "us," and "our" utterances and directive speech acts issued to explore how managers and co-workers perform agency and power in meetings. This distinctive book will shed light into the influence of language on the actions and relationships of managers and co-workers in business meetings, and will be of interest to applied linguists and discourse analysts in the field of business discourse in addition to business professionals in management and finance.